Reducing poverty and inequality through tax-benefit reform and the minimum wage: The UK as a case-study - A. B. Atkinson; Chrysa Leventi; Brian Nolan; Holly Sutherland; Iva Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Atkinson's book Inequality: What Can Be Done? (Harvard University Press, 2015) sets out a range of concrete proposals aimed at reducing income inequality, which cover a very broad span but include major changes to the income tax and social transfers system and the minimum wage. These are framed with specific reference to the UK but have much broader relevance in demonstrating how substantial the impact on inequality of such measures could be. This paper assesses the first-round effects of these tax, transfer and minimum wage reforms on income inequality and poverty based on a microsimulation approach using EUROMOD. The reforms involve a significantly more progressive income tax structure, a major increase in the minimum wage to the level which is estimated to represent the "Living Wage", and alternative routes to reforming social transfers - either to strengthen the social insurance element or to restructure the entire system as a Participation Income (a variant of Basic/Citizen's Income). The results show how the first-round effects of either set of tax and transfer proposals would be to substantially reduce the extent of income inequality and relative income poverty and the paper draws out how the two approaches differ in their effects. The additional impact of raising the minimum wage to the Living Wage is modest, reflecting in particular the position of beneficiaries in the household income distribution and the offsetting effects on household income of the withdrawal of means-tested cash transfers.
Keywords: D31; H24; I38; 330; income inequality and poverty; work incentives; tax-benefit reforms; microsimulation